Keanekaragaman Budaya: Strategi Efektif Pendidikan Multikultural di SMA Muhammadiyah 2 Sidoarjo - Suprianto, Guntur; Suprayitno, Kabul (MASALIQ, 2025)
This study aims to explore multicultural education strategies at SMA Muhammadiyah 2 Sidoarjo and the challenges encountered in their implementation. Using a qualitative approach with a case study design, the research was conducted over six months, from January to June 2024. Data were collected through in-depth interviews, participatory observations, and document analysis involving school principals, teachers, students, and educational staff. The findings indicate that effective multicultural education strategies include integrating multicultural values into the curriculum, utilizing extracurricular activities to enhance cultural understanding, and providing teacher training in diversity management. Additionally, key challenges include educators’ lack of experience in supporting cultural diversity, resistance from some students and parents, and limited resources. The study's implications emphasize the need to enhance teacher capacity through multicultural training, develop a more inclusive curriculum, and strengthen school policies that support diversity. This research provides valuable insights for educational institutions in fostering an inclusive and harmonious learning environment and encourages further studies with a broader scope of schools to enrich perspectives on implementing multicultural education in Indonesia.